Pengaruh Temperatur Deposisi Lapisan Penyangga Aluminium Nitrida terhadap Struktur Kristal dan Morfologi Film Tipis GaN dengan Metoda DC Unbalanced Magnetron Sputtering - Dadi Rusdiana (Institut Teknologi Bandung, 2006)
Gallium nitride thin films were grown on (0001) sapphire substrates by DC unbalanced magnetron sputtering using of aluminum nitride buffer layer. The properties of GaN thin films were improved by optimization of the growth temperature of buffer layers between 450 °C to 700 °C. Results showed that GaN film properties such as crystal structures and morphological properties were improved. XRD characterization shows that there was most probability to create a better of crystal structure with orientations of (1011) and (1120) with FWHM 0.3° and 0.6° respectively if the growth temperature of buffer layer was 450 °C.